2020
DOI: 10.1038/s41598-020-67497-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased both PD–L1 and PD–L2 expressions on monocytes of patients with hepatocellular carcinoma was associated with a poor prognosis

Abstract: Anti-programmed cell death-1 (PD-1) antibodies has been approved to treat HCC. Some PD-1 ligands (PD–L1 and PD–L2) negative tumors respond to treatment of anti-PD-1 antibodies, and this fact may be caused by the expression of PD-1 ligands on non-tumor cells. PD–L1 was recently found to be expressed on CD14+ cells from cancer patients. We investigate PD-1 ligands expression on CD14+ cells of patients with HCC and the role of CD14+ cells in an antitumor response. In this study, 87 patients diagnosed with HCC wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Specifically, PD-L1 + PD-L2 + CD14 + cells were cocultured with CD8 + cells isolated from syngeneic patients, resulting in the antitumor activity of CD8 + cells being suppressed against HepG2 cells and Huh7 cells. Meanwhile, their antitumor activity was restored following treatment with a PD-1 antibody, that is, CD14 + cells suppressed the antitumor activity of CD8 + cells via the PD-L/PD-1 pathway, which can be restored by PD-1 antibodies [ 19 ]. Similarly, it has been reported that PD-L1 on dendritic cells mediates CD8 + T-cell antitumor activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, PD-L1 + PD-L2 + CD14 + cells were cocultured with CD8 + cells isolated from syngeneic patients, resulting in the antitumor activity of CD8 + cells being suppressed against HepG2 cells and Huh7 cells. Meanwhile, their antitumor activity was restored following treatment with a PD-1 antibody, that is, CD14 + cells suppressed the antitumor activity of CD8 + cells via the PD-L/PD-1 pathway, which can be restored by PD-1 antibodies [ 19 ]. Similarly, it has been reported that PD-L1 on dendritic cells mediates CD8 + T-cell antitumor activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, PD-L1/L2 expression in other antitumor effector cells, such as CD4 T cells, CD8 T cells, B cells, and mast cells, were not examined. However, we have previously reported that the expression of both PD-L1 and PD-L2 in monocytes is associated with poor prognosis [ 19 ]. We conclude that monocytes expressing both PD-L1 and PD-L2 may play a key role in antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, M1 macrophages can induce PD-L1 expression on hepatocarcinoma cells by IL-1β effect [ 64 ]. These data suggest an important role of macrophages in modulating CD8 T cell exhaustion in HCC by promoting a immunotolerant environment [ 65 ] and by up-regulating themselves both PD-L1 and PD-L2 expression [ 66 ]. However, PD-L1 expression on macrophages could also have a positive input because it correlates with CD8 T cell infiltration and increased OS after treatment [ 67 ], probably in the case of M1-like macrophage infiltration [ 17 ].…”
Section: Role Of Pd-1-expressing Hcc-specific Cd8 T Cell Response In Hcc Controlmentioning
confidence: 99%
“…Studies have shown HCC cells with overexpression of programmed death-1 (PD-1) can elicit weaker immune reactions by suppressing T-cell response and resulting in uncontrolled cell division [ 8 , 9 ]. Amplified MHC class II molecule expression in hepatocellular carcinoma result in T-cell anergy as co-stimulatory molecules cannot be identified by other antigen-presenting cells.…”
Section: Introductionmentioning
confidence: 99%